Back Cover: Synthesis of Wavelength‐Shifting Fluorescent DNA and RNA with Two Photostable Cyanine–Styryl Dyes as the Base Surrogate Pair (ChemistryOpen 4/2017). Issue 4 (21st July 2017) - Steinmeyer, Jeannine; Rönicke, Franziska; Schepers, Ute; Wagenknecht, Hans‐Achim
Abstract : The Back Cover picture shows two new DNA/RNA building blocks, which were synthesized and successfully incorporated into DNA and RNA by using automated solid‐phase chemistry. The two cyanine–styryl dyes, as base‐pair surrogates in DNA as well as in RNA, efficiently form an energy‐transfer pair. The energy transfer between dyes controls the color of the emission between red (double strand) and green (single strand), giving rise to promising tools for molecular imaging.More information can be found in the Full Paper by H.‐A. Wagenknecht and co‐workers onpage 514 in Issue 6, 2017 (DOI:10.1002/open.201700059 ).